Agent red (Columbia Tristar Home Video, 2001)
Matt Hendricks (Dolph Lundgren) is the US Navy's top Marine Special Operations Commander and he is facing his toughest challenge yet - to personally escort the deadliest viral weapon on the planet back to a safe storage facility. Abroad the submarine the USS New Orleans, the deadly chemical is locked away and the mission is business as usual until a Russian terrorist group boards the vessel and takes the crew hostage. Their plan - to spread the virus over a major American city. Miles below the ocean's surface, with the US Navy attacking from above, and violent terrorists attacking from above, Hendricks must battle the enemy and keep the deadly virus sealed , before it escapes and annihilates humanity.